Public Spaces for Leisure: Green area use in Presidente Prudente – SP - Ulloffo, Luan Moreira; Lima, Angelika Franklin de; Granado, Danielli Cristina (National Journal of City Management, 2025)
Objective – This study aims to identify and characterize the most frequently visited public leisure spaces associated with the natural environment by the community of two schools located in the outskirts of the city, as well as to understand the motivations behind these choices. Methodology – Bibliographic and documentary research, a survey of public leisure spaces in Presidente Prudente, on-site visits to characterize the areas, and consultations with the sampled population to understand the level of involvement, preferences, and frequency of visits to these places by the school community. Originality/Relevance – This research was driven by the ongoing discussion about the importance of green areas designated for public use in Presidente Prudente, particularly for students of public schools and the broader community of schools located in peripheral neighborhoods Results – The Do Povo Park is the most frequently visited public space by youth from public schools and members of the school community in Presidente Prudente (SP), primarily used for family outings. However, it was observed that these young individuals rarely visit the analyzed public spaces, with distance being the main factor preventing them from frequenting these leisure areas. Theoretical/Methodological Contributions – This study contributes to the understanding of the main factors influencing the choice and frequency of public leisure space usage by the population, highlighting the social relevance of these areas in meeting citizens’ recreational needs. These spaces can promote physical activity and social interaction, thus contributing to improvements in physical, mental, and spiritual health. Social and Environmental Contributions – This research helps to understand the relationship between public leisure spaces and population motivations, aiming to support the development of effective and integrated public policies that promote healthier lifestyles, enhance the value of urban green spaces, and strengthen a culture of environmental care, reviving traditional values of harmonious coexistence between humans and nature.